2003
DOI: 10.1159/000072816
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Verb Processing in Frontal Variant-Frontotemporal Dementia: A Dysexecutive Symptom

Abstract: Object and action naming and comprehension were tested in frontotemporal dementia (frontal variant, FTD), in Alzheimer’s disease (AD) and in controls. Although lower scores were obtained by all groups, we can confirm that actions were proportionally more impaired in FTD. The correlation between action naming deficit and severity of dementia was stronger in this group than in AD. The correlation analysis also suggested that the naming disorder was different in nature in FTD (mostly a dysexecutive deficit) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
(26 reference statements)
3
41
1
1
Order By: Relevance
“…In this study, nouns, verbs and adjectives were trained. However, verbs have been shown to be more difficult to retrieve than nouns within spontaneous speech due to factors such as the requirement to generate morphological verb inflections (in agrammmatic speakers) [49], and higher cognitive demands of naming verbs than nouns [45,50].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nouns, verbs and adjectives were trained. However, verbs have been shown to be more difficult to retrieve than nouns within spontaneous speech due to factors such as the requirement to generate morphological verb inflections (in agrammmatic speakers) [49], and higher cognitive demands of naming verbs than nouns [45,50].…”
Section: Discussionmentioning
confidence: 99%
“…We have also drawn attention to the fact that the use of static depictions of actions to probe verb/action naming and comprehension may account for a verb/action disproportionate deficit in patients with reduced executive resource (see, for evidence, d 'Honincthun & Pillon, 2008). Actually, higher demand in executive control for verb than for noun processing has been frequently advanced as a possible source of a verb disproportionate deficit, especially in patients with degenerative brain disease (e.g., Cotelli et al, 2006Cotelli et al, , 2007Grossman et al, 2008;Rhee et al, 2001;Silveri, Salvigni, et al, 2003). Rhee and colleagues (2001) and Silveri, Salvigni, and colleagues (2003) provided evidence for a significant correlation between a disproportionate deficit in verb naming (Silveri, Salvigni, et al, 2003) or verb comprehension (Rhee et al, 2001) and executive resource limitation in patients with dementia of Alzheimer's type and patients with the frontal variant of frontotemporal dementia (see also Grossman et al, 2008, for similar evidence with patients with amyotrophic lateral sclerosis).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies (see Appendix, Table A1(a)), the patients presented a noun or a verb disproportionate deficit in a picture naming task, but, in a comprehension task (the most often, a word-picture matching task), the patients were either not impaired at all or as impaired for both categories of words (Bates, Chen, Tzeng, Li, & Opie, 1991;Berndt, Mitchum, Haendiges, & Sandson, 1997;Bird, Howard, et al, 2000;Breedin, Saffran, & Schwartz, 1998;Cotelli et al, 2006;De Renzi & di Pellegrino, 1995;Hernandez, Costa, Sebastian-Galles, Juncadella, & Rene, 2007;Hillis et al, 2006;Kambanaros, 2008;Kim & Thompson, 2000, 2004Laiacona & Caramazza, 2004;Miceli, Silveri, Nocentini, & Caramazza, 1988;Miozzo, Soardi, & Cappa, 1994;Shapiro & Caramazza, 2003a, 2003bSilveri & Di Betta, 1997;Silveri, Perri, et al, 2003;Silveri, Salvigni, Cappa, Della Vedova, & Puopolo, 2003;Sörös, Cornelissen, Laine, & Salmelin, 2003;Yip, Law, HsuanChih, & Li, 2006;Zingeser & Berndt, 1988). There is also a group study (Appendix, Table A1(b)) of patients with semantic dementia who showed a noun disproportionate deficit in a word -picture matching task but whose performance in a picture naming task revealed no significant difference between nouns and verbs (Cotelli et al, 2006).…”
Section: Patterns Of Grammatical Category-specific Deficits Inconsistmentioning
confidence: 99%
See 1 more Smart Citation
“…Vergeleken met AD blijven het episodisch Neuropraxis (2006) 10:49-52 51 geheugen en de visuospatie¨le functies tot in een verder gevorderd stadium van de ziekte intact (Binetti et et al, 2000). Bij verdenking op FTD verdient het aanbeveling het onderzoek uit te breiden met 'frontale' tests, zoals verbale woordproductie, abstract redeneren, mentale flexibiliteit en het kunnen negeren van interfererende condities (Slachevsky et al, 2004;Silveri et al, 2003). Daarnaast zijn er taken in ontwikkeling die het vermogen tot empathie en emotionele cognitie in kaart brengen (Miller et al, 2003).…”
Section: Conclusieunclassified